The role of strengthening leadership behaviour on the psychological contract in primary and secondary schools - Gokyer, Necmi (Education Assoc South Africa, 2020)
In the study reported on here we aimed to determine the role of strengthening leadership behaviour on the psychological contract in primary and secondary schools. The population was a total of 7,772 teachers (3,627 primary school teachers and 4,145 middle school teachers) working in the districts of Baglar, Kayapmar, Sur and Yenisehir in Diyarbakir during the 2017-18 academic year. A total of 621 teachers selected by random sampling participated in the study. Data were collected through the following scales developed by Kocak (2016): the School Administrators' Level of Conformity to Psychological Contract Scale and the Teachers' Level of Conformity to Psychological Contract Scale. Teacher perceptions of school managers' demonstration of empowering leadership behaviour were measured with the Reinforcing Leadership Behaviours Scale developed by Konczak, Stelly and Trusty (2000) and adapted to Turkish by Aras (2013). Teacher perceptions of school administrators' levels of compliance with psychological contracts (SACPC) were found to be moderate and teachers' levels of compliance with the psychological contract (OPSUD) was high. Teacher perceptions of school administrators in terms of empowering leadership behaviour (ELB) were found to be high.
Keywords: employee empowerment; empowering leadership behaviour; primary school; psychological contract; secondary school; teacher